Social costs of inequality: Heterogeneous endowments in public-good experiments - Claudia Keser; Andreas Markstädter; Martin Schmidt; Cornelius Schnitzler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
We compare voluntary contributions to the financing of a public good in a symmetric setting to those in asymmetric settings, in which four players have different, randomly allocated endowments. We observe that a weak asymmetry in the endowment distribution leads to the same contribution level as symmetry. Players tend to contribute the same proportion of their respective endowment. In a strongly asymmetric setting, where one player has a higher endowment than the three other players together, we observe significantly lower group contributions than in the other settings. The super-rich player does not contribute significantly more than what the others contribute on average and thus a much lower proportion of the endowment.
Keywords: C92; D63; H41; 330; experimental economics; linear public good; income heterogeneity